2015
DOI: 10.1111/vcp.12272
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal studies of cardiac troponin I concentrations in serum from male cynomolgus monkeys: resting values and effects of oral and intravenous dosing on biologic variability

Abstract: Background: There is a paucity of information regarding cardiac troponin (cTn) concentrations in peripheral blood of nonhuman primates (NHP). Even less is known regarding cTn concentrations in monkeys that are restrained for oral or intravenous (iv) dosing. Objectives: The objectives of these studies were to (1) determine cardiac troponin I (cTnI) concentration in resting Cynomolgus monkeys and investigate biologic variability in cTnI concentration over time, (2) determine cTnI changes in restrained monkeys gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Skeletal muscle injury is further supported in the animal with an elevation in CK values on day 1 prior to dosing, without concurrent increase in cTnI concentrations. Schultze et al (2015) have performed similar experiments to those discussed above. They looked at cTnI concentrations in resting NHP as well as those that had been shamed dosed by oral gavage or intravenous saline injection.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Skeletal muscle injury is further supported in the animal with an elevation in CK values on day 1 prior to dosing, without concurrent increase in cTnI concentrations. Schultze et al (2015) have performed similar experiments to those discussed above. They looked at cTnI concentrations in resting NHP as well as those that had been shamed dosed by oral gavage or intravenous saline injection.…”
Section: Discussionmentioning
confidence: 97%
“…Other potential mechanisms that have been suggested that can lead to the release of troponin without necrosis include apoptosis, normal myocyte turnover, cellular release of proteolytic troponin degradation products, increased cellular wall permeability, or formation and release of membranous blebs (White 2011). This is further supported by the very low fluctuating levels of cTnI that can be detected in the circulation of normal animals using the newer ultrasensitive assays such as the Singulex Errena cTnI (Schultze et al 2015(Schultze et al , 2009. Although these mechanisms for release of cardiac troponin from intact cells cannot be totally ruled out, minimal myocellular necrosis leading to transient elevation of cardiac troponin also cannot be ruled out.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Schultze et al previously reported blood cTnI measurements in intact Sprague-Dawley rats and cynomolgus monkeys. Their experiments consisted of careful measurements made over multiple time points under resting conditions after saline administration by oral gavage (Schultze et al 2009 , 2015 ). Although these studies provided much-needed data for future cTnI research, serial blood samplings were conducted using an automated cannulation method, which is different from the standard procedures of most toxicity studies (i.e., repeated needle injections under restraint).…”
Section: Introductionmentioning
confidence: 99%